Fatigue reliability of welded joints accounting for uncertainties in weld geometry - Huiying Gao (Advances in Mechanical Engineering, 2022)
Fatigue reliability assessment of welded joints can consider the uncertainties from various sources and can establish the design criteria and inspection plans. The present paper aims to address the uncertainties explicitly. The notch strain approach that accounts for the effects of the misalignment, local notch, and crack-like imperfection, which is referred to as secondary notch, is employed. Sensitivity analyses indicate that uncertainties in misalignment, flank angle, weld toe radius together with secondary notch are all important sources of the total uncertainty. The practical difficulty in the determination of the uncertainty models of the geometric parameters is discussed, and the acceptance limits for fabrication are used to derive the uncertainty models. And finally, the impacts of acceptance limits on the fatigue reliability of welded joints are assessed. The results indicate that the weld toe radius and secondary notch depth significantly affect the reliability index and the fatigue reliability increases with the weld quality of the welded joint becomes higher.